The Role of Knowledge Management in Improving Performance of Human Resources – A Field Study on the General Organization for Technical and Vocational Training, Riyadh Region – - Alsaqhan, Ghadair Abdurahman; Almostadi, Wala Abdullah (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to identify how knowledge management plays a role in improving human resources, it also aimed to identify the realities of knowledge updating of the institution, and knowledge disseminating and distributing among workers.The research sample consists of the employees of the top departments 11.419 of the general organization for vocational training in three departments: the national training department, the general administration of quality and training, the general administration for development and curriculum design, in the Riyadh region, the study used a descriptive and analytical approach to address the research subject. knowledge management has been also mentioned as an important and positive impact on the efficiency of the organization's internal processes and the quality of performance.The results have been as follows: there is a positive statistical significant correlation between the knowledge diagnosis and measuring the quality of human resource performance, the value of the correlation between them was (0.577), at a significant level (0.00), which is a value less than (0.01),there is a positive statistical significant correlation between updating knowledge and measuring the quality of human resources performance, as the value of the correlation between them reached (0.682), at a significant level (0.00), which is a value less than (0.01),there is a positive statistical significant correlation between the disseminating and distributing of knowledge and the measuring of the quality of human resource performance (0.705), at a significant level (0.00), which is a value less than (0.01), as the higher the diagnosis of updating, disseminating and distributing knowledge, the higher the quality of human resource performance.The most important recommendations of researchers: The necessity for the institution to have the ability to identify its employees who possess knowledge related to its fields of activities.The necessity for the institution to provide material and moral rewards to its employees for their efforts to gain new knowledge that supports its activities.Reliance on objective and fair standards in order to truly reveal the levels of employee performance, which leads to avoiding problems among workers.
Keywords: knowledge management; human resources; performance; organization; training